Productivity effects of processing and ordinary export market entry: A time-varying treatments approach - Sourafel Girma; Holger Görg (Kiel Centre for Globalization (KCG), 2021)
China's policy of encouraging export processing has been the topic of much discussion in the academic literature and policy debate. We use a recently developed econometric approach that allows for time varying "treatments" and estimate economically and statistically significant positive causal effects of entering into export processing and ordinary export markets on subsequent firm level productivity. These productivity effects are shown to be larger than those accruing to firms who enter into ordinary exporting. Interestingly, the estimation of quantile treatment effects shows that the positive effects do not accrue similarly to all types of firms, but are strongest for those at the low to medium end of the distribution of the productivity variable. We also find that export processors gain more when entering the industrialised North rather than the South, while this does not appear to matter much for ordinary exporting.
Keywords: F14; F61; O14; 330; export processing; firm performance; China; time varying treatments